Neurons of the inferior olive respond to broad classes of sensory input while subject to homeostatic control. (11th April 2019) - Ju, Chiheng; Bosman, Laurens W.J.; Hoogland, Tycho M.; Velauthapillai, Arthiha; Murugesan, Pavithra; Warnaar, Pascal; van Genderen, Romano M.; Negrello, Mario; De Zeeuw, Chris I.
Abstract : Key points: Purkinje cells in the cerebellum integrate input from sensory organs with that from premotor centres. Purkinje cells use a variety of sensory inputs relaying information from the environment to modify motor control. Here we investigated to what extent the climbing fibre inputs to Purkinje cells signal mono‐ or multi‐sensory information, and to what extent this signalling is subject to recent history of activity. We show that individual climbing fibres convey multiple types of sensory information, together providing a rich mosaic projection pattern of sensory signals across the cerebellar cortex. Moreover, firing probability of climbing fibres following sensory stimulation depends strongly on the recent history of activity, showing a tendency to homeostatic dampening. Abstract: Cerebellar Purkinje cells integrate sensory information with motor efference copies to adapt movements to behavioural and environmental requirements. They produce complex spikes that are triggered by the activity of climbing fibres originating in neurons of the inferior olive. These complex spikes can shape the onset, amplitude and direction of movements and the adaptation of such movements to sensory feedback. Clusters of nearby inferior olive neurons project to parasagittally aligned stripes of Purkinje cells, referred to as 'microzones'. It is currently unclear to what extent individual Purkinje cells within a single microzone integrate climbing fibre inputs from multiple sources of different sensory origins, and to what extent sensory‐evoked climbing fibre responses depend on the strength and recent history of activation. Here we imaged complex spike responses in cerebellar lobule crus 1 to various types of sensory stimulation in awake mice. We find that different sensory modalities and receptive fields have a mild, but consistent, tendency to converge on individual Purkinje cells, with climbing fibres showing some degree of input‐specificity. Purkinje cells encoding the same stimulus show increased events with coherent complex spike firing and tend to lie close together. Moreover, whereas complex spike firing is only mildly affected by variations in stimulus strength, it depends strongly on the recent history of climbing fibre activity. Our data point towards a mechanism in the olivo‐cerebellar system that regulates complex spike firing during mono‐ or multi‐sensory stimulation around a relatively low set‐point, highlighting an integrative coding scheme of complex spike firing under homeostatic control. Key points: Purkinje cells in the cerebellum integrate input from sensory organs with that from premotor centres. Purkinje cells use a variety of sensory inputs relaying information from the environment to modify motor control. Here we investigated to what extent the climbing fibre inputs to Purkinje cells signal mono‐ or multi‐sensory information, and to what extent this signalling is subject to recent history of activity. We show that individual climbing fibres convey multiple types of sensory information, together providing a rich mosaic projection pattern of sensory signals across the cerebellar cortex. Moreover, firing probability of climbing fibres following sensory stimulation depends strongly on the recent history of activity, showing a tendency to homeostatic dampening.